Karakteristik Kampas Rem Dari Komposit Serbuk Arang Tempurung Kelapa dan Serbuk Tulang Sapi - Novianto, Arief; Ismail, Rifky; Saputra, Bagus Ari (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
The number of vehicles being added in Indonesia is increasing every year, so the demand for auto parts is bound to increase as well. The brake pad is one of the most significant and rapidly changing components. Asbestos regulations begin to restrict brake linings. Asbestos brake pads are being phased out in favor of more environmentally friendly or asbestos-free alternatives since they constitute a health and environmental risk. This is why it is suggested that brake pads be made from asbestos-free materials. One of them is to develop the application of a mixture of coconut charcoal powder and cow bone powder as a composite material for brake pads. In addition to coconut shell charcoal and beef bone, other materials used to make composite brakes are aluminium powder, epoxy resin and MgO. These materials are printed by hot pressing at 180°C. This was an experimental research in which three different preparations were modeled. Furthermore, composite brake pads are evaluated for hardness, wear, and heat resistance in order to determine the optimal model. According to the test results, sample 1 has the maximum hardness value of 71.44 HV. Sample 1 has the lowest abrasion value of 2.62 mm2/kg, making it difficult to wear. In the heat resistance test, all three samples meet the SAE J661 requirement because the surface is not damaged during the 360°C test, such as stamping, cracking, puncture, or warping. Thus, sample 1 is the best of the three, with the highest hardness value, the least abrasion, and no damage in the heat resistance test.